Knowledge and skills necessary for product innovation in SMEs manufacturing industry in Malaysia - Md Noor, Haris (2013)
Product innovation and its spill-overs into new products, technologies and productive capacity are deemed to be important determinants of firms’ productivity growth, competitive advantage and ultimately their survival. In spite of its pivotal role, the process that leads to the production of innovation is still poorly understood among the Malaysian industries. The aim of this research is to identify the knowledge and skills necessary for product innovation in the manufacturing sector of SMEs in Batu Pahat, Johor. This research was conducted using quantitative approach, where questionnaires was used as the major instrument in data collection. The data was analysed by using the Statistical Package for Social Science (SPSS) programme . The research analysis outcomes showed that customer and market knowledge is the most dominant knowledge necessary for product innovation. The mean score was 4.22 for both which have high tendency towards product innovation. The overall outcome for the skills and knowledge showed high tendency towards the necessity for product innovation. Further analysis is suggested to be conducted to get better understanding of the real relationship between skills and knowledge towards product innovation.